Exploring the Nexus Between E-Business Processes and Organizational Performance: Can Technological Opportunism Play Any Role? - Al-Omari, Mohammad Ahmad; AlZgool, Mahmoud Radwan Hussein; Ahmed, Umair; Pahi, Munwar Hussain; AlMaamary, Qais (Frontiers in Psychology, 2022)
The digitization of business processes has gained much scholarly and practical attention in the recent past. To understand their effectiveness, particularly in connection to organizational performance, the current study developed and tested a comprehensive framework. Through obtaining data from 350 manufacturing businesses, the study investigated using Smart PLS3 and found a significant influence of online procurement, channel management, and service delivery capabilities on organizational performance. Furthermore, the study also found the significant direct and moderating potential of technological opportunism to harness organizational performance. The study concludes that e-business processes serve as crucial resources and capabilities for businesses to achieve their goals and objectives. The study offers contributory implications for theory and practice indicating for strategic investment of e-business processes for businesses aiming to boost their performance.